Bartolomé Bennassar y las inquisiciones - Doris Moreno (Les Cahiers de Framespa)
This text reflects on some of the most essential contributions made by Bartolomé Bennassar to the Inquisition history analysing its influence and relevance in contemporary studies on the Holy Office: the complexity of inquisitorial repression in its multiple forms and levels through the policy of presence (visits, edicts, familiares...), the pedagogy of fear (the auto-de-fe, the secrecy, the infamy) and the attention to all the symbolic components of the exercise of representation that implied the inquisitorial action.